2008
DOI: 10.1007/s11426-008-0106-4
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic phosphorylcholine-protected water-soluble Ag nanoparticles

Abstract: The water-soluble Ag nanoparticles capped with novel zwitterionic thioalkylated phosphorylcholine were synthesized. The Ag nanoparticles showed remarkable stability in saline media with salt concentrations as high as 2.0 mol/L and plasma using UV-vis absorption spectroscopy. Similarly, compared with tiopronin and citrate-protected Ag nanoparticles, the zwitterionic phosphorylcholine Ag nanoparticles did not precipitate out of solution when charged polyelectrolytes or biopolymers were added. The zwitterionic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The modified polymeric membranes showed excellent biocompatibility with cells, proteins, tissues and blood. Similar works were also carried out by several other research groups [20][21][22][23][24].…”
supporting
confidence: 64%
“…The modified polymeric membranes showed excellent biocompatibility with cells, proteins, tissues and blood. Similar works were also carried out by several other research groups [20][21][22][23][24].…”
supporting
confidence: 64%
“…Furthermore, it has also been reported that coating by zwitterionic structure is helpful in evading uptake by RES and achieving long blood circulation time 53–55. Zwitterionic polymers have been coated on the surface of nanoparticles like silver,56 gold,57, 58 silica,59, 60 quantum dots61 and magnetite nanoparticles62 to enhance biocompatility and stability or to prolong in vivo circulation time. The inconsistent results from the above studies may be due to the difference of nanoparticle types, variation in stability of nanoparticles resulting from surface charge, the nature of charged groups, and other confounding factors such as inhomogeneous particle sizes.…”
Section: Surface Propertiesmentioning
confidence: 99%
“…Inspired by the electrically‐neutral head group of the naturally occurring phospholipid phosphatidylcholine, Jin et al . synthesized the thioalkylated phosphorylcholine, 11‐mercaptoundecylphosphorylcholine (HS‐PC), and used it to prepare zwitterionic‐coated silver nanoparticles (structure 12 , Figure ).…”
Section: Zwitterionic Coatings: a Viable Route Forward?mentioning
confidence: 99%